Кібербезпека у сфері публічних фінансів - Качула, Світлана Валентинівна; Kachula, Svitlana (Видавничий дім "Гельветика", 2025)
У статті розглянуто актуальні питання кібербезпеки у сфері публічних фінансів в умовах цифрової трансформації державного управління. Показано, що зростання кібератак на фінансові органи та інформаційні системи вимагає переходу від реактивної до проактивної моделі захисту. Проаналізовано технологічні, організаційні та інституційні інструменти забезпечення кіберзахисту, серед яких системи виявлення та запобігання вторгненням, використання криптографії, блокчейн-технологій, аудити безпеки, розвиток державно-приватного партнерства і транскордонної співпраці. Наголошено на необхідності вдосконалення нормативно-правової бази у згоді з міжнародними стандартами, імплементації директив ЄС, активного співробітництва з міжнародними мережами CERT. Зроблено висновок, що комплексний підхід, який поєднує технічні рішення, організаційні заходи і міжнародну узгодженість, є ключем до створення стійкої системи кіберзахисту публічних фінансів України. The article examines the issue of cybersecurity in the field of public finance in the context of the rapid digital transformation of public administration and the global growth of cyber threats. It is emphasized that financial stability of the state, transparency of budget processes and citizens’ trust in governmental institutions increasingly depend on the reliability of digital infrastructure and the ability to counteract complex cyberattacks. The study identifies key risks for public finance systems, including targeted attacks on treasury platforms, attempts of unauthorized access to databases, phishing campaigns against employees of financial authorities, as well as large-scale ransomware incidents affecting continuity of financial operations. The research highlights the urgent necessity to move from a reactive approach, limited to responding to incidents, to a proactive cybersecurity model, based on prediction, prevention, early detection, and continuous monitoring of threats. Special attention is devoted to technological and organizational tools of protection such as intrusion detection and prevention systems, cryptographic methods of data protection, blockchain solutions ensuring transparency and immutability of financial transactions, as well as artificial intelligence applications in anomaly detection and fraud prevention. In addition, the importance of organizational mechanisms such as regular security audits, staff training programs, and development of national cyber response centers is underlined. The article stresses that successful protection of public finance requires not only technical measures, but also institutional cooperation between state bodies, private sector, and international partners. Harmonization of Ukrainian legislation with EU directives, in particular NIS2, and active participation in international information exchange networks such as CERT are defined as strategic priorities. The conclusion is drawn that only a comprehensive approach, integrating technological innovations, organizational frameworks, and international coordination, will allow Ukraine to create a sustainable cybersecurity system for public finance, capable of resisting current and future digital challenges.
Cybersecurity in public finance
Keywords: кібербезпека; cybersecurity; інформаційна безпека; information security; захист даних; data protection; публічні фінанси; public finance; фінансова інформація; financial information; цифрові технології; digital technologies; кіберзагрози; cyber threats; управління ризиками; risk management; державний сектор; public sector; інформаційна інфраструктура; information infrastructure